Intranasal midazolam for the treatment of seizures in children in rural India - Babbar, Neha; Nanda, Sanjiv; Rohilla, Aarti (Indian Journal of Child Health, 2020)
Background: About 5% of healthy children experience at least one convulsive episode in their lifetime with onset during childhood in more than half the cases. The current evidence suggests that prolonged seizures are best stopped with early treatment. Objective: The objective of the study was to assess the role of intranasal administration of midazolam for seizure cessation at home by caregiver in semi-urban and rural settings. Materials and Methods: A total of 50 children in the age group of 6 months–14 years were included in the study, who previously had a history of convulsions and were on regular follow-up. The study was conducted over a period of 6 months. The parents were instructed to give intranasal midazolam (INM) if seizure activity lasted for more than 3 minutes and the need of giving it 2nd time if the seizure was not aborted and to bring the child to nearest pediatrics emergency set up for the further management. Results: The subjects were divided into three groups according to age: Group A consisted of children between 6 months and 4 years, Group B of 4 and 9 years, and Group C had 9 and 14 years old children. Average duration of aborting seizures before INM use was 16.22 min and after its use was 4.66 min. Seizures were aborted in 45 children within 10 min. Conclusion: INM is safe and efficacious in aborting seizures at home in semi-urban and rural settings.